DESAIN DAN ANALISA VELG MOBIL 15 INCH TIPE ALUMINIUM ALLOY 6061 MELALUI SIMULASI PENGUJIAN DYNAMIC CORNERING FATIGUE SESUAI STANDAR SAE J 328 - Gamayel, Adhes; Ikhsannudin, Moh. Nova; Zaenudin, Mohamad (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2024)
The rim is the part of the wheel that gets the force and tension because of holding the vehicle's weight in a stationary or moving position. Wheels have a critical zone related to force and stress in the area called the spoke. This study aims to compare several wheel models that have been modified to find the minimum critical value. The wheels that were analyzed consisted of model 1 wheels with a spoke radius of 4 mm, model 2 wheels with a spoke radius of 8 mm and model 3 wheels with a spoke radius of 12 mm. The research method was carried out using a static structural analysis method with a reverse engineering approach. The research was carried out in several stages related to dynamic cornering fatigue testing and loading. The results of this test are compared with the standard of the Society of Automotive Engineers (SAE) J 328. Wheel design using Autodesk Inventor 2016 software and simulated using ANSYS Workbench R1 2022 software. The results of the simulation are the equivalent elastic strain, equivalent von misses, and fatigue life values ​​of the three-wheel models. Model 1 alloy wheel design has an equivalent von misses value of 75.022 MPa, an equivalent elastic strain of 0.0016627 mm/mm and a fatigue life value of 1,000,000 rounds. The model 2 alloy wheel design has an equivalent von Misses value of 119.53 MPa, an equivalent elastic strain of 0.001862 mm/mm and a fatigue life value of 1,000,000 rounds. The model 3 alloy wheel design obtained an equivalent von misses value of 136.96 MPa, an equivalent elastic strain of 0.0019852 mm/mm and a fatigue life value of 841,040 rounds. Of all the wheel models, seen from the simulation results, they meet the SAE J 328 standard